Feedback Dilemma in Higher Education: Perspectives and Practices of Faculty in a Public University: https://doi.org/10.55966/assaj.2025.4.1.093 - Aliya Kousar; Dr. Zahra Jabeen; Dostdar Hussain* (`, 2025)
The study examined the faculty's perception, preferences, and practice of providing feedback at a public university in Gilgit-Baltistan, Pakistan. A qualitative research design was used, focusing on the design of case studies. Four professors from the Faculty of Arts and Humanities were specially selected to participate in the research. Data was collected using a semi-structured questionnaire. Classroom observations and documentary analysis were used to strengthen the reliability of findings and to triangulate data. The results showed that faculty members primarily conceptualised feedback as a response to student performance, to promote academic growth and development. Written and oral feedback were both recognised as essential, but oral feedback emerged as the most commonly used feedback method. Participants stressed that their choice of feedback method was influenced by the context and nature of the challenge. It is noteworthy that while the practices of some of the professors were in line with the established approaches, in others, inconsistencies were found through observation and documentary evidence. Teachers should therefore be provided with training courses organised by HEC. In addition, teachers should carry out a survey on student preferences for feedback at the departmental level. Key words: Perceptions, preferences, practices, written feedback, oral feedback, higher education